MODEL KONSERVASI SUMBERDAYA AIR SEBAGAI UPAYA MEMPERTAHANKAN KEBERLANJUTAN AIR DI SUB DAS AEK SILANG - Irwan Valentinus Sihotang; Sudarmadji Sudarmadji; Setyawan Purnama; Baiquni Baiquni (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2016)
ABSTRACT Continuous availability of water as a basic requirement for survival and for the purposes of production so need to be maintained. The availability of water resources is strongly influenced by environmental and natural resource management is done by humans. Water resource conservation efforts through the increased role of the parties is expected sustainability of water can be maintained. The research objective is to formulate a model of conservation of water resources and efforts needed for water sustainability can be maintained. Data were collected using questionnaires and interviews, and then analyzed descriptively by using a technique AHP (Analytical Hierarchy Process). The results of the analysis with AHP technique showed that the main priority of the alternative strategy of water resources conservation activities is to preserve water (38.70%). The effort to preserve water is technically civilian conservation, forest and land rehabilitation (RHL), control the use of water, maintenance of water resources and coaching/mentoring for communitie. Keywords: Sustainable water, Water resource conservation, AHP, Preserve water